Mengungkap Peran Ilustrasi Musik dalam Membangun Mood, Nuansa, dan Suasana pada Film ‘Tonggak Tuo’ - Indra Syukma (SENDRATASIK UNP, 2023)
Musical illustration plays a crucial role in establishing the mood, nuances, and atmosphere in films. This study delves into two main aspects: 1) how directors and composers apply mood, nuances, and atmosphere through musical illustration in various scenes, and 2) the significance of musical illustration in the film "Tonggak Tuo." The researcher employs a qualitative descriptive research method, presenting data in both textual and graphical forms. The primary focus of this study revolves around the role of music illustration in films as a builder of mood, nuances, and atmosphere, as per Himawan Pratista's film music illustration theory. Data collection methods encompass document review, interviews, and literature review. Analytically, this research directly observes the content of "Tonggak Tuo" to investigate the role of music illustration, employing content analysis and interpretative techniques. The results affirm that musical illustrations play a pivotal role in constructing the mood, nuances, and atmosphere within the film "Tonggak Tuo."